2006
DOI: 10.1108/13673270610670911
|View full text |Cite
|
Sign up to set email alerts
|

The effect of knowledge management practices on firm performance

Abstract: Purpose -This research proposes to study the connection between knowledge management practices and firm performance.Design/methodology/approach -Theoretical relations are tested through an empirical study carried out on 222 Spanish firms in the biotechnology and telecommunications industries.Findings -This paper shows how the firms that adopt knowledge management practices obtain better results than their competitors.Research limitations/implications -The subject of principles has not been considered a dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(63 citation statements)
references
References 17 publications
7
40
0
3
Order By: Relevance
“…The positive association of HRM practices and KM was also asserted by Theriou and Chatzoglou (2014), Kuo (2011) and Donate and Guadamillas (2011). Furthermore, Shehata (2015), Gharakhani and Mousakhani (2012), Marqués and Simón (2011), Zack et al (2009), Mills and Smith (2011 and Kuo (2011) confirmed the significant impact of KM on OP.…”
Section: Hypotheses Testingsupporting
confidence: 52%
“…The positive association of HRM practices and KM was also asserted by Theriou and Chatzoglou (2014), Kuo (2011) and Donate and Guadamillas (2011). Furthermore, Shehata (2015), Gharakhani and Mousakhani (2012), Marqués and Simón (2011), Zack et al (2009), Mills and Smith (2011 and Kuo (2011) confirmed the significant impact of KM on OP.…”
Section: Hypotheses Testingsupporting
confidence: 52%
“…Específicamente, los resultados señalan, en primer lugar, un claro apoyo para el supuesto de que la gestión del conocimiento influye positivamente en los resultados empresariales, en coherencia con la literatura (Palacios Marqués y Garrigós Simón, 2006;Hsiao et al, 2011;Huang, 2011;López Nicolás y Meroño Cerdán, 2011;Rašula et al, 2012), que mayoritariamente ha destacado que la gestión del conocimiento puede mejorar el rendimiento y la competitividad de las organizaciones. En este sentido, cabe destacar la importancia de concentrar esfuerzos y recursos en la gestión activa del conocimiento, pues esto permitirá que las empresas puedan seguir siendo competitivas y crecer.…”
Section: Conclusiones Y Discusiónunclassified
“…Mientras que algunos estudios han destacado que la gestión del conocimiento favorece los resultados empresariales (Palacios Marqués y Garrigós Simón, 2006;Chen, Monahan y Feng, 2009;Hsiao, Chen y Chang, 2011;Huang, 2011;López Nicolás y Meroño Cerdán, 2011;Rašula, Bosilj Vukšić e IndiharŠtemberger, 2012), otros apoyan que son las prácticas de gestión de recursos humanos las que contribuyen a mejorar dichos resultados (Huselid, 1995;Becker y Gerhart, 1996;Youndt, Snell, Dean y Lepak, 1996;Collins y Clark, 2003;Chen y Huang, 2009). Adicionalmente, ciertas investigaciones proponen que la gestión del conocimiento y la gestión de los recursos humanos están estrechamente relacionadas (Oltra, 2005;Haesli y Boxall, 2005;Afiouni, 2007;Theriou y Chatzoglou, 2008;Wang, Chiang y Tung, 2012), habiéndose decantado la mayoría por analizar el efecto mediador de la gestión del conocimiento en la relación entre gestión de recursos humanos y resultados de la empresa (Jackson, Schuler y Jiang, 2014).…”
Section: Introductionunclassified
“…For example, Andreeva and Kianto (2012) highlight the shortage of empirical studies demonstrating the connection between knowledge management and organizational performance. However, nowadays there are more and more studies showing evidence about the impacts of knowledge management on organizational performance (e.g., Andreeva and Kianto 2012;Darroch 2005;Inkinen 2016;Massingham 2014;Palacios Marqués and Garrigós Simón 2006). Therefore, other explanations are needed in order to fully understand why knowledge management has not become as popular as could have been expected.…”
Section: Literature Reviewmentioning
confidence: 90%